2020
DOI: 10.1002/advs.202000915
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles (NPs)‐Meditated LncRNA AFAP1‐AS1 Silencing to Block Wnt/β‐Catenin Signaling Pathway for Synergistic Reversal of Radioresistance and Effective Cancer Radiotherapy

Abstract: Resistance to radiotherapy is frequently encountered in clinic, leading to poor prognosis of cancer patients. Long noncoding RNAs (lncRNAs) play important roles in the development of radioresistance due to their functions in regulating the expression of target genes at both transcriptional and posttranscriptional levels. Exploring key lncRNAs and elucidating the mechanisms contributing to radioresistance are crucial for the development of effective strategies to reverse radioresistance, which however remains c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…Meanwhile, there is a strong connection between EMT and HCC (Tong et al, 2020). The Wnt/β-catenin signaling pathway is involved in the development of various human cancers and one of the most well-characterized oncogenic pathway in HCC (Hoshida et al, 2009;Huang et al, 2019;Bi et al, 2020;Wang et al, 2020). A variety of key cellular processes including proliferation, apoptosis, migration and invasion are involved in the progression of HCC in a Wnt/β-catenin-dependent manner (Huang et al, 2020;Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is a strong connection between EMT and HCC (Tong et al, 2020). The Wnt/β-catenin signaling pathway is involved in the development of various human cancers and one of the most well-characterized oncogenic pathway in HCC (Hoshida et al, 2009;Huang et al, 2019;Bi et al, 2020;Wang et al, 2020). A variety of key cellular processes including proliferation, apoptosis, migration and invasion are involved in the progression of HCC in a Wnt/β-catenin-dependent manner (Huang et al, 2020;Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…18 operative radiotherapy. 138 They also found higher lncAFAP1-AS1 expression was correlated with poor disease-free survival and overall survival of TNBC patients. 138 These results demonstrated that high lncAFAP1-AS1 expression is associated with radio-resistance of TNBC patients, and the expression level of lncAFAP1-AS1 in tumour tissues could be used to predict the outcome of TNBC radiotherapy.…”
Section: Ln Crna Ac Ts a S B I Omark Er For D Iag Nos Is And Prog Nmentioning
confidence: 93%
“…Recently, Bi et al reported that higher lncAFAP1‐AS1 expression was detected in the patients with local recurrence, using the surgically resected tumour tissues of TNBC patients receiving postoperative radiotherapy 138 138 . These results demonstrated that high lncAFAP1‐AS1 expression is associated with radio‐resistance of TNBC patients, and the expression level of lncAFAP1‐AS1 in tumour tissues could be used to predict the outcome of TNBC radiotherapy.…”
Section: Lncrna Acts As Biomarker For Diagnosis and Prognosis In Tnbcmentioning
confidence: 95%
“…Upregulation of AFAP1-AS1 promotes BRCA cell proliferation and invasion but inhibits cell apoptosis in vitro, while overexpression of AFAP1-AS1 promotes tumor growth in vivo and is associated with poor prognosis of TNBC patients [ 82 ]. Bi et al [ 83 ] selected AFAP1-AS1 from the locally recurrent BRCA samples after RT and the radioresistant BRCA cell line MDA-MB-231. They discovered that lncAFAP1-AS1 was not only upregulated in radioresistant cells and tumor tissues but was also associated with a low survival rate of BRCA patients from the TCGA database.…”
Section: Lncrnas In Regulating the Radioresistance Of Breast Cancermentioning
confidence: 99%